Semaphorin-3E Produced by Immature Dendritic Cells Regulates Activated Natural Killer Cells Migration - Alamri, Abdulaziz; Rahman, Rahmat; Zhang, Manli; Alamri, Abeer; Gounni, Abdelilah S.; Kung, Sam K. P. (Frontiers in Immunology, 2018)
Natural Killer (NK) cells and dendritic cells (DC) are two innate immune cells that are critical in regulating innate and adaptive immunity. Cellular functions and migratory responses of NK or DC can be further regulated in NK-DC crosstalk that involves multiple cytokine signals and/or direct cell-cell contacts. Semaphorin-3E (Sema-3E) is a member of a large family of Semaphorin proteins that play diverse regulatory functions in different biological systems upon its binding to the cognate receptors. However, possible role(s) of Sema-3E on the regulation of NK-cell functions has not been elucidated. Here, we first demonstrated that DC and NK cells expressed Sema-3E and its receptors, respectively. To formally address the importance of DC-derived Sema-3E in regulating NK-cell migration, we compared in vitro migratory responses of activated NK cells towards different conditioned media of dendritic cells (immature, LPS- or Poly I:C-stimulated) derived from Sema-3E+/+ or Sema-3E-/- mice. We observed that activated NK cells exhibited enhanced migrations towards the conditioned medium of the immature Sema-3E-/- DC, when compared to that of the immature Sema-3E+/+ DC. Addition of exogenous recombinant Sema-3E to the conditioned medium of the Sema-3E-/- immature DC abrogated such enhanced NK-cell migration. Our current work revealed a novel role of Sema-3E in limiting NK-cell migrations toward immature DC in NK-DC crosstalk.